1993
DOI: 10.1055/s-0038-1649627
|View full text |Cite
|
Sign up to set email alerts
|

Orgaran (Org 10172) or Heparin for Preventing Venous Thrombosis after Elective Surgery for Malignant Disease? A Double-Blind, Randomised, Multicentre Comparison

Abstract: SummaryThis double-blind, randomised, multicentre trial in 513 patients having elective surgery for intra-abdominal or intrathoracic malignancy compared the efficacy and safety of venous thrombosis (VT) prophylaxis using 750 anti-factor Xa units of Orgaran (a mixture of low molecular weight heparinoids) given subcutaneously (sc) twice-daily with that of twice-daily injections of 5,000 units Standard heparin. The main study endpoints were the development of postoperative VT detected by 125I-fibrinogen leg scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 33 publications
0
30
0
1
Order By: Relevance
“…The present study compared the thromboprophylactic efficacy and safety of LMWH and UFH in gynecologic patients after cancer surgery. The use of LMWH showed an identical prophylactic effect as UFH and recent studies using LMWH demonstrated comparable incidences of DVT after cancer surgery ranging between 0.5% to 10.4% (14)(15)(16)(17)(18)(19). The location of the DVTs in our patients was similar to those in other studies (16,18).…”
Section: Discussionmentioning
confidence: 88%
“…The present study compared the thromboprophylactic efficacy and safety of LMWH and UFH in gynecologic patients after cancer surgery. The use of LMWH showed an identical prophylactic effect as UFH and recent studies using LMWH demonstrated comparable incidences of DVT after cancer surgery ranging between 0.5% to 10.4% (14)(15)(16)(17)(18)(19). The location of the DVTs in our patients was similar to those in other studies (16,18).…”
Section: Discussionmentioning
confidence: 88%
“…Так, у лиц с острым нарушением мозгового кровообращения, сопровождающимся парезами и параличами ниж них конечностей, частота верификации ВТ на фоне стандартной профилактики, включающей эластич ную компрессию, интермиттирующую пневмоком прессию, прямые антикоагулянты, находится в ин тервале 4-23% со средним значением 11,6% [17][18][19][20][21][22][23][24][25]. При хирургическом лечении онкологических заболеваний частота развития ВТ составляет 6,25-55,5% (в среднем 15,9%) на фоне применения анти коагулянтов и компрессионной терапии [26][27][28][29][30][31][32][33][34][35][36]. У больных нейрохирургического профиля на фоне применения механических, фармакологических средств профилактики и их комбинации частота ин струментальной верификации послеоперационных ВТ колеблется от 1,5 до 26,3% и в среднем составля ет 12,5% [37][38][39][40][41][42][43][44][45][46][47].…”
Section: флебология 1 2015unclassified
“…Recommendation: There is also no difference in the occurrence of bleeding and increased risk of intraoperative or postoperative bleeding regarding the use of low molecular weight heparin or unfractionated heparin in most evidence extrapolated to patients undergoing general surgery or by abdominal malignancy. Nevertheless, the use of thromboprophylaxis compared with not using heparin perioperatively, may increase postoperative bleeding events 3,13,35,42,43,47,64,72,74,94,95,98,103,105,122 The contraindications for thromboprophylaxis in patients that carry digestive tract surgery -extrapolating to elderly with cancer without surgery -may be particularly hypersensitivity to heparin, septic endocarditis, hemorrhagic stroke, documented bleeding diathesis, treatment with anticoagulant or platelet antiaggregant, and renal or hepatic dysfunction 12,14,15,16,22,31,37,38,42,72,86,95,103. (Recovered = 5806; first selection = 142; included = 13)…”
Section: Recommendationmentioning
confidence: 99%